Literature Review: Potential Activity of Natural Ingredients as Antibiofilm Agents against Pathogenic Bacteria in Vitro - Muktiali, Abdul Hamid; Hidayati, Agriana Rosmalina (Jurnal Biologi Tropis, 2025)
Natural materials have great potential as sources of active antibiofilm compounds that can inhibit or destroy the biofilm matrix of pathogenic bacteria. Based on this, this review article was compiled as a systematic review journal to trace, select, and analyse various scientific publications related to the antibiofilm activity of natural materials over the past 10 years. The review focuses on the in vitro testing methods used in these journals, namely the Microtiter Plate Assay, tube test, direct microscopic observation, and post-test only control group design. The review results indicate that differences in testing methods yield varying levels of sensitivity and accuracy in observations; however, all demonstrate that antibiofilm efficacy is significantly influenced by phytochemical content, test concentration, and bacterial type. Thus, the selection of appropriate testing methods and comprehensive phytochemical analysis are key factors in supporting the development of effective, applicable, and environmentally friendly antibiofilm formulations based on natural materials.